2014
DOI: 10.1111/pme.12439
|View full text |Cite
|
Sign up to set email alerts
|

Self-Loathing Aspects of Depression Reduce Postoperative Opioid Cessation Rate

Abstract: Objective We previously reported that increased preoperative Beck Depression Inventory II (BDI-II) scores were associated with a 47% (95% CI 24%–64%) reduction in the rate of opioid cessation following surgery. (1) We aimed to identify the underlying factors of the BDI-II (affective/cognitive vs. somatic) associated with a decreased rate of opioid cessation after surgery. Methods We conducted a secondary analysis of the data from a previously reported (1) prospective, longitudinal, observational study of opi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 70 publications
1
15
1
Order By: Relevance
“…Previous studies on outcomes following TKA using traditional approaches to postoperative analgesia have reported extended opioid use and delayed functional recovery. In recent studies of patients receiving various postoperative treatments (e.g., oral medications, local anesthetic-based nerve blocks, transcutaneous electrical nerve stimulation, intravenous acetaminophen), average opioid consumption is often greatest during the immediate postoperative period (e.g., average daily morphine equivalent dosage [MED] of approximately 30-170 mg during postoperative days 0-3) (7,(39)(40)(41)(42)(43); fewer than 30% of patients had ceased opioid use by four weeks following TKA, and the median time to opioid cessation was approximately 45-60 days (4,6,7). In the present study, average daily MED during postoperative days 0-3 was approximately 22 mg, a majority (4 of 7; 57%) of subjects reported opioid cessation within the first week following surgery, and the median time to opioid cessation was six days.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies on outcomes following TKA using traditional approaches to postoperative analgesia have reported extended opioid use and delayed functional recovery. In recent studies of patients receiving various postoperative treatments (e.g., oral medications, local anesthetic-based nerve blocks, transcutaneous electrical nerve stimulation, intravenous acetaminophen), average opioid consumption is often greatest during the immediate postoperative period (e.g., average daily morphine equivalent dosage [MED] of approximately 30-170 mg during postoperative days 0-3) (7,(39)(40)(41)(42)(43); fewer than 30% of patients had ceased opioid use by four weeks following TKA, and the median time to opioid cessation was approximately 45-60 days (4,6,7). In the present study, average daily MED during postoperative days 0-3 was approximately 22 mg, a majority (4 of 7; 57%) of subjects reported opioid cessation within the first week following surgery, and the median time to opioid cessation was six days.…”
Section: Discussionmentioning
confidence: 99%
“…Postoperative pain is most often treated with opioid analgesics, however, these have a high risk of misuse and debilitating side effects (e.g., sedation, dizziness, nausea, constipation, urinary retention, and sleeping problems) that often interfere with physical rehabilitation and function. Recent studies show that opioid use continues at least four weeks following TKA in over 70% of patients, with the median time to opioid cessation approximately 45–60 days .…”
Section: Introductionmentioning
confidence: 99%
“…69 In a mixed surgical cohort, elevated preoperative Beck Depression Inventory-II (BDI-II) scores were a significant predictor of prolonged opioid use independent of pain in a mixed surgical cohort 66 Further factor analysis identified self-loathing symptoms of the BDI-II as a significant predictor of prolonged opioid use rather than somatic symptoms, which could be confounded by pain and other medical comorbidities in a surgical cohort. 7072 The primary determinants of postoperative opioid cessation appear unrelated to the duration of postoperative pain and preoperative pain intensity both at the future surgical site and elsewhere over the entire body. 66 Thus, specific efforts to promote opioid cessation are warranted aside from focusing solely on optimizing pain management in the postoperative period.…”
Section: Predictors Of Chronic Opioid Use After Surgerymentioning
confidence: 99%
“…11 Post-surgically, opioid use is commonly quantified either by dose or by time to opioid cessation. 12,13 Perioperative studies have yielded mixed findings for pain catastrophizing, with some reporting a direct relationship with morphine dose delivered either by patient controlled analgesia devices 14 or by hospital staff, 15 while other studies reported no association 16 or an inverse association. 17 Findings from a recent longitudinal study of 145 musculoskeletal trauma surgery patients suggested that pain catastrophizing predicted delayed opioid cessation after surgery.…”
Section: Introductionmentioning
confidence: 99%